Carbonylative Cyclization of o-Halobenzoic Acids for Synthesis of N-Substituted Phthalimides Using Polymer-Supported Palladium–N-Heterocyclic Carbene as an Efficient, Heterogeneous, and Reusable Catalyst - Khedkar, Mayur V.; Khan, Shoeb R.; Dhake, Kishor P.; Bhanage, Bhalchandra M. (Synthesis, 2012)
The carbonylative cyclization of o-iodobenzoic acid with a variety of primary amines and carbon monoxide (1 bar) using a polymer-supported palladium–N-heterocyclic carbene complex (PS-Pd-NHC) as the catalyst gives N-substituted 1H-isoindole-1,3(2H)-diones (phthalimides) in good to excellent yields with a short reaction time. The catalyst is efficient, heterogeneous, and phosphine-free, it exhibited remarkable activity and it is also recyclable (4 consecutive cycles). The use of methyl o-iodobenzoate as the substrate under these conditions also gave N-substituted 1H-isoindole-1,3(2H)-diones, but with lower yields. Cyclization of o-iodobenzyl alcohol with carbon monoxide under these conditions gave isobenzofuran-1(3H)-one (phthalide).
Keywords: carbonylative cyclization; heterogeneous catalysis; N-heterocyclic carbene; phosphine-free; phthalimides; isoindoles